RNF144A-VRK2-G3BP1 axis regulates stress granule assembly - Sung Wook Kim; Jae Lee; Kyung Won Jo; Young-Hun Jeong; Won Sik Shin; Kyong-Tai Kim (Cell Death Discovery)
Abstract Under the cellular stress, stress granules (SGs) help survival and proliferation of the cell. Unfortunately, the same SGs help unwanted cancer cells under stressful environment, including anti-cancer chemotherapy treatment. While SGs elevate the cancer cell’s resistance to chemotherapy, the mechanism behind the formation of SGs in cancer cell under chemotherapy treatment is still to be revealed. Here, we identified that the level of VRK2 and the phosphorylation of its novel substrate, G3BP1, are reduced when the cellular stress was increased by sodium arsenite (SA) or cisplatin treatment. We also demonstrated that the level of RNF144A is increased in response to the stress and further downregulates VRK2 through proteasomal degradation in various types of cancer cells. Furthermore, inhibition of SG formation by the overexpression of VRK2 sensitized the cells to the stress and chemotherapy. Together, our study establishes an RNF144A-VRK2-G3BP1 axis that regulates SG formation and suggest its potential usage in anti-cancer therapy.